Analisis Framing Pemberitaan Dukungan PDI Perjuangan pada Sistem Pemilu Proporsional Tertutup pada Kompas.com dan Mediaindonesia.com - Teddy Malaka; Astrid Brenda Maharani (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
During the 2024 General Election, the Open Proportional Election system was challenged in the Constitutional Court by a number of politicians. When the judicial review took place, PDI Perjuangan, as the winning political party in the 2019 elections, expressed support for the Closed Proportional Election System. This support was conveyed through a number of news reports in the mass media. In this qualitative research, the framing carried out by Kompas.com reveals the reasons Why PDI Perjuangan supports a closed proportional system as well as the advantages of a closed proportional system and the rejection of a closed proportional election system is considered a form of defense of democracy. While mediaindonesia.com emphasizes the majority of rejection of the closed proportional electoral system, showing that this rejection is considered a common thing that then results in an agreement to reject the Closed Proportional Election system as a form of exemplary democracy. This research shows that media conglomeration affects the determination of news sources.